Fames of success: the inspiring journey of Fauzi Manan - UiTM, Faculty of Business and Management (UiTM, 2024)
Starting a business is never easy, but for Fauzi Manan, an alumnus of FBM, the journey from student to successful entrepreneur was fueledby by a deep passion for creativity, organization, and impact. As the founder of FAMES Management, Fauzi has built a name for himself in the industry, providing top-tier event management solutions under one roof.